Experimental demonstration of tractor millimeter wave beam propulsion - Masayuki Takahashi; Toshiki Yamada; Ryutaro Minami; Tsuyoshi Kariya; Kohei Shimamura (Scientific Reports)
Abstract Tractor millimeter-wave beam propulsion (TMiP), which obtains a propulsive force by receiving a high-power tractor beam from the front side of the vehicle, was proposed for space missions such as rocket launches from Earth and planetary takeoff missions. A beam irradiation experiment with a gyrotron device was conducted for a model rocket with a polytetrafluoroethylene (PTFE) lens to collect the tractor beam power, facilitating gas breakdown and plasma generation at the focal point. A high-pressure gas was formed via plasma heating, interacting with the PTFE lens mounted on the front of the vehicle and generating a propulsive force for rocket launching. A parametric study was conducted by changing the pulse width, which showed that the maximum thrust performance was achieved when the plasma front propagating toward the beam source did not protrude from the air-breathing intake at the front of the vehicle. Additionally, computational simulations for electromagnetic wave propagation and compressible fluid dynamics indicated that the thrust performance could be improved by decreasing the rocket diameter due to shock wave concentration.